MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII A SMPN 6 TANJUNG PADA MATERI CAHAYA MENGGUNAKAN MODEL PEMBELAJARAN JIGSAW - ASPIHANI MATLEH (Universitas Lambung Mangkurat, 2012)
This study aims to find out improvement student’s achievement, activities, skill laboratory, and responses on optics using Jigsaw models. Subjects were a class of eighth grade students of SMPN 6 Tanjung. This research used class-action-research design with 2 cycles, each cycle consisting of three meetings. The number of students in this study amounted 20 people. data collected by tests, questionnaires, observations, and analyzed by quantitative descriptive. The results showed that (1) student learning outcomes using Jigsaw models has increased, (2) students responded positively to the use of Jigsaw models in optics of learning. Key words : Jigsaw Models, optics, cycle, quantitative descriptive.